2004
DOI: 10.1111/j.1349-7006.2004.tb02180.x
|View full text |Cite
|
Sign up to set email alerts
|

What are the reasons for negative phase III trials of molecular‐target‐based drugs?

Abstract: The results of molecular-biological studies of cancer are changing the way we diagnose and treat cancer. Target n an attempt to modulate specific molecular targets in tumor cells and the tumor environment, the emphasis in anticancer drug discovery has shifted from an empirical approach characterized by random screening of a variety of natural and synthetic compounds by means of cell-based cytotoxicity assays to more rational and mechanistic molecular screening. 1-5)The concept of molecular-target-based therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Inhibitors targeting signaling molecules that are overexpressed and activated in cancer have shown only modest clinical benefit when used as single agents (1, 2). One explanation for this may rest in recent data demonstrating that extracellular signals are transmitted through a network of proteins rather than through hierarchical signaling pathways (35).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitors targeting signaling molecules that are overexpressed and activated in cancer have shown only modest clinical benefit when used as single agents (1, 2). One explanation for this may rest in recent data demonstrating that extracellular signals are transmitted through a network of proteins rather than through hierarchical signaling pathways (35).…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, therapies developed against cancer cells cultured for high proliferation rates are effective in vitro and in preclinical in vivo models but achieve only modest clinical results. 7 Understanding the effects of hypoxia on cancer cells is essential to appreciating the discordance between the efficacy of therapeutics that target cancer cell proliferation in vitro and their effects on tumor growth. 8 Hypoxic regions of a tumor are capable of de-differentiating the resident cancer cells, facilitating their adaptation to invasive growth and metastatic colonization.…”
Section: Introductionmentioning
confidence: 99%
“…Targeted agents that inhibit specific molecules implicated in tumor cell growth have been classified according to (1) the site of action (tumor-specific and tumor-environment-specific), (2) the mechanism of action (the target pathways associated with tumor growth and survival), and (3) pharmaceutical formulations (small molecular compounds and macromolecules such as antibodies) (Saijo 2004). These classifications, however, are derived from the viewpoint of pharmaceutical preclinical development.…”
Section: Classification Of Targeted Agents For Clinical Developmentmentioning
confidence: 99%
“…Two small, but crucial randomized phase III trials in patients with EGFR mutation-positive advanced non-small cell lung cancer showed that the progression-free survival, the primary endpoint of these trials, was much better for gefitinib than for platinum-based chemotherapy (Maemondo et al 2010;Mitsudomi et al 2010). Therefore, the clinical development of novel targeted agents for cancer therapy is likely to be impeded without appropriate consideration of the clinical trial design (Saijo 2004). …”
Section: Introductionmentioning
confidence: 99%